In vivo and in silico anti-inflammatory mechanism of action of the semisynthetic (−)-cubebin derivatives (−)-hinokinin and (−)-O-benzylcubebin. Issue 2 (15th January 2017) - Lima, Thaís C.; Lucarini, Rodrigo; Volpe, Angelica C.; de Andrade, Carolina Q.J.; Souza, Alice M.P.; Pauletti, Patricia M.; Januário, Ana H.; Símaro, Guilherme V.; Bastos, Jairo K.; Cunha, Wilson R.; Borges, Alexandre; da Silva Laurentiz, Rosangela; et al.
Graphical abstract: Abstract: (−)-Cubebin (CUB), isolated from seeds of Piper cubeba, was used as starting material to obtain the derivatives (−)-hinokinin (HK) and (−)-O-benzyl cubebin (OBZ). Using paw edema as the experimental model and different chemical mediators (prostaglandin and dextran), it was observed that both derivatives were active in comparison with both negative (5% Tween® 80 in saline) and positive (indomethacin) controls. The highest reduction in the prostaglandin-induced edema was achieved by OBZ (66.0%), while HK caused a 59.2% reduction. Nonetheless, the dextran-induced paw edema was not significantly reduced by either of the derivatives (HK or OBZ), which inhibited edema formation by 18.3% and 3.5%, respectively, in contrast with the positive control, cyproheptadine, which reduced the edema by 56.0%. The docking analysis showed that OBZ presented the most stable ligand-receptor (COX-2 – cyclooxygenase-2) interaction in comparison with CUB and HK.